2016
DOI: 10.18001/trs.2.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Nicotine Content Expectancies Affect Initial Responses to Smoking

Abstract: Objectives We sought to determine if negative responses to reduced nicotine content (RNC) cigarettes during open-label trials result from smokers’ (negative) expectancies. We examined the effects of nicotine content description – independent of actual nicotine content – on subjective responses (craving reduction, withdrawal suppression, mood changes, and sensory ratings) and smoking behaviors (topography measures and carbon monoxide [CO] boost). Methods Thirty-six 12-hour-abstinent daily smokers completed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…Participants’ expectancies about RNC cigarettes may have influenced attrition [29], although expectancies would likely similarly influence acceptability under federal nicotine regulation. Like most RNC cigarette trials, this study did not replicate the exact environment of mandated nicotine reduction; for example, because use periods were 10 days only, findings may not generalize to longer exposure (i.e., less willingness to use RNC cigarettes for a 6-week vs. 35-day trial may increase attrition).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants’ expectancies about RNC cigarettes may have influenced attrition [29], although expectancies would likely similarly influence acceptability under federal nicotine regulation. Like most RNC cigarette trials, this study did not replicate the exact environment of mandated nicotine reduction; for example, because use periods were 10 days only, findings may not generalize to longer exposure (i.e., less willingness to use RNC cigarettes for a 6-week vs. 35-day trial may increase attrition).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our sample of heavy-smoking, mainly white, non-menthol smokers from a single city may not represent the larger smoking population. Participants' expectancies about RNC cigarettes may have influenced attrition [29], although expectancies would probably influence acceptability similarly under federal nicotine regulation. Like most RNC cigarette trials, this study did not replicate the exact environment of mandated nicotine reduction; for example, because use periods were 10 days only, findings may not generalize to longer exposure (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate whether under-reporting non-study cigarette use is common in different VLN cigarette switching studies, we applied this method to data from one study using cigarettes manufactured by Philip Morris USA [22] and two studies using cigarettes from the Vector Group [9,23]. Figure 4 presents the resulting average non-study CPD estimates and shows that there was under-reporting of non-study cigarette CPD across all three studies, although at lower magnitude than in Donny et al [2].…”
Section: Magnitude Of Under-reporting Across Different Studiesmentioning
confidence: 99%
“…For example, nicotine content expectancies significantly influence craving reduction, mood, wakefulness, calmness, concentration, satisfaction from smoking, and hunger reduction. [19][20][21][22][23] Other studies have found significant influences of nicotine content expectancies for other nicotine delivery products such as sprays and inhalers on satisfaction and craving relief. [24][25][26] These studies suggest the amount of nicotine that smokers believe is in a product can supersede their experience of receiving a different nicotine amount even at relatively high doses.…”
Section: Introductionmentioning
confidence: 99%